28-Year Survival following Several Metastasectomies, Going through 8th Line Systemic Therapy in a Case of mRCC - A. Magdy; K. Bretterbauer; S. Hruby; T. Kunit; D. Colleselli; G. Janetschek; M. Mitterberger (Case Reports in Urology)
Metastatic renal cell carcinoma (mRCC) has been one of the most treatment-resistant cancers because of its unpredictable clinical course, resistance to chemo- and radiotherapy, and the limited response to immunotherapy and targeted agents. We present a case of long-term survival, that is, 28 years, after primary diagnosis (longest survival in the literature up to our knowledge) with mRCC after several metastasectomies (from local site recurrence, liver, and lung) and eight lines of systemic targeted therapy. This case report shows how crucial is the regular follow-up of patients with RCC after primary management and positive impact of early metastasectomy and systemic targeted therapy in case of mRCC on patients’ condition and overall survival.